2019
DOI: 10.15678/ier.2019.0502.04
|View full text |Cite
|
Sign up to set email alerts
|

Determining the contributory factors to successful succession and post-succession performance of family-owned SMEs in South Eastern Nigeria

Abstract: This study seeks to determine the contributory factors to successful succession and post-succession performance. And the role of these factors in the post-succession financial and non-financial performance of family-owned SMEs in South Eastern Nigeria. Research Design & Methods: The adopted quantitative methodology is interview. In each of the purposively selected 25 family-owned SMEs, the incumbent, a sibling of the incumbent and a top level manager were interviewed. In all, 75 respondents were interviewed. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 50 publications
0
5
0
Order By: Relevance
“…In Nigeria, studies have found that the factors that enhance the post-succession performance of family businesses include the institution of succession planning process and the characteristics of the founders of the family-owned businesses (Agbim, 2019). Founders of family-owned businesses who have sustained and managed businesses beyond the first generation utilised innovative strategies (Akinbami et al ., 2019).…”
Section: Introductionmentioning
confidence: 99%
“…In Nigeria, studies have found that the factors that enhance the post-succession performance of family businesses include the institution of succession planning process and the characteristics of the founders of the family-owned businesses (Agbim, 2019). Founders of family-owned businesses who have sustained and managed businesses beyond the first generation utilised innovative strategies (Akinbami et al ., 2019).…”
Section: Introductionmentioning
confidence: 99%
“…An effectively developed succession plan provides for a smooth transition in management and ownership (Chrisman, Sharma & Yoder, 2019). Agbim (2019) identified succession planning as a contributory factor to successful succession in a family-owned business.…”
Section: Suggested Citationmentioning
confidence: 99%
“…Family Businesses in Spain contribute 85 percent of the business sector, 70 percent of the national GDP, and 70 percent of employment in the private sector (Galván, Martínez & Rahman, 2017). A study of family businesses firms in Japan shows Kongo Gumi construction firm is the world's oldest familyowned business which began operation in 578 AD till the end of 2005, spanning over 39 generations, and the company's succession planning practices facilitated business survival over fourteen centuries (Agbim, 2019).…”
Section: Suggested Citationmentioning
confidence: 99%
“…In Nigeria, most family-owned enterprises fail to make it to the second generation, and even fewer make it to the third (Ayodeji, 2019). Family businesses are enterprises in which family members who are connected by blood, adoption, or marriage have a substantial role in all or key strategic decisions made by the company, having ramifications for the company's performance, productivity, survival, and development (Agbim, 2019). A family business possesses the following four traits: it is operated by a single family, hires non-family members, and has an independent board of directors.…”
Section: Introductionmentioning
confidence: 99%
“…The family business employs a specific number of relatives. A family business is held by family members and is driven by family ties to achieve the family's purpose through several generations (Agbim, 2019).…”
Section: Introductionmentioning
confidence: 99%